The sublime : from antiquity to the present - Costelloe, Timothy M. (Cambridge University Press, 2012)
This volume offers readers a unique and comprehensive overview of theoretical perspectives on "the sublime," the singular aesthetic response elicited by phenomena that move viewers by transcending and overwhelming them. The book consists of an editor's introduction and fifteen chapters written from a variety of disciplinary perspectives. Part One examines philosophical approaches advanced historically to account for the phenomenon, beginning with Longinus, moving through eighteenth and nineteenth century writers in Britain, France and Germany, and concluding with developments in contemporary continental philosophy. Part Two explores the sublime with respect to particular disciplines and areas of study, including Dutch literature, early modern America, the environment, religion, British Romanticism, the fine arts and architecture. Each chapter is both accessible for nonspecialists and offers an original contribution to its respective field of inquiry.